2011
DOI: 10.1007/s00455-011-9363-z
|View full text |Cite
|
Sign up to set email alerts
|

The Digastric Muscle is Less Involved in Pharyngeal Swallowing in Rabbits

Abstract: The swallowing reflex is centrally programmed by the lower brain stem, the so-called swallowing central pattern generator (CPG), and once the reflex is initiated, many muscles in the oral, pharyngeal, laryngeal, and esophageal regions are systematically activated. The mylohyoid (MH) muscle has been considered to be a "leading muscle" according to previous studies, but the functional role of the digastric (DIG) muscle in the swallowing reflex remains unclear. In the present study, therefore, the activities of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In particular, the superior laryngeal nerve (SLN), which innervates the valleculae and the upper portion of the larynx to the level of the vocal folds, triggers the swallow (4,21,50). Unilateral and bilateral lesion of the internal branch of the SLN results in significant aspiration (4,5,14), and electrical stimulation of the iSLN is sufficient to trigger a pharyngeal swallow (21,35,51).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the superior laryngeal nerve (SLN), which innervates the valleculae and the upper portion of the larynx to the level of the vocal folds, triggers the swallow (4,21,50). Unilateral and bilateral lesion of the internal branch of the SLN results in significant aspiration (4,5,14), and electrical stimulation of the iSLN is sufficient to trigger a pharyngeal swallow (21,35,51).…”
mentioning
confidence: 99%
“…pharyngeal swallow (35,43,51), and pharyngeal swallows can be elicited by injecting fluid into the valleculae in decerebrate animals (6,7,45). However, extensive investigation has shown that characteristics of the pharyngeal swallows can be modulated (21,27,32) by a variety of oral (17,42) and pharyngeal (44) sensory triggers.…”
mentioning
confidence: 99%
“…The suprahyoid muscles, particularly the anterior belly of the digastric and the mylohyoid, dominantly contribute to jaw-opening ( Khan and Bordoni, 2021 ). The digastric muscle helps in depressing and retracting the mandible functionally but is less involved in deglutition, at least in animals ( Doty and Bosma, 1956 ; Tsujimura et al, 2012 ). Conversely, the mylohyoid muscle also functions to elevate the floor of the mouth and the tongue during deglutition or speaking while the geniohyoid muscle contributes to upward and forward movements of the hyoid, and hence widening of the passage for the bolus during deglutition.…”
Section: Discussionmentioning
confidence: 99%
“…The suprahyoid muscles, particularly the anterior belly of the digastric and the mylohyoid, dominantly contribute to jawopening (Khan and Bordoni, 2021). The digastric muscle helps in depressing and retracting the mandible functionally but is less involved in deglutition, at least in animals (Doty and Bosma, 1956;Tsujimura et al, 2012). Conversely, the mylohyoid muscle also functions to elevate the floor of the mouth and the tongue during deglutition or speaking while the geniohyoid muscle contributes to upward and forward movements of the hyoid, and hence widening of the passage for the bolus during deglutition.…”
Section: Difference In Sequence Changes Among Foodsmentioning
confidence: 99%